The Influence of Brand Image and Service Quality towards Customer Loyalty in Pharmacy Retail Stores - Putri, Natalia Christiani; Fristiohady, Adryan; Ruslin, Ruslin; Wahyuni, Wahyuni; Akib, Nur Illiyyin (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The pharmaceutical business in Indonesia, including in Kendari City, has shown a positive growth trend in recent years. Pharmacies compete by applying different marketing strategies, with some adopting a conventional model and others utilizing a modern retail approach, such as self-service pharmacies. Pharmacy X, a modern self-service pharmacy, is perceived to have a strong brand image and standardized services. This study evaluates the influence of brand image and perceived service quality on customer loyalty in a modern pharmacy setting. Data were collected via a Google Form questionnaire from 100 customers who had visited twice during the period of October to November 2024. The data were analyzed using descriptive statistics and Structural Equation Modelling (SEM) with SmartPLS. Results revealed that brand image significantly affects customer loyalty, while service quality does not show a significant impact. Brand image contributed to customer loyalty with an influence value of 33.3% based on the R-squared value, indicating a moderate effect, and a Q-squared value of 0.275, reflecting moderate predictive accuracy. Brand image is critical in enhancing customer loyalty at Pharmacy X, while service quality may require further improvement or reassessment in its current implementation.